The untargeted metabolomic analysis of Ammodaucus leucotrichus Coss. & Dur. seeds reveals previously undescribed polar lignans and terpenoids - Kisiriko, Musa; Bitchagno, Gabin T. M.; Noleto-Dias, Clarice; Naboulsi, Imane; Anastasiadi, Maria; Terry, Leon A.; Sobeh, Mansour; Beale, Michael H.; Ward, Jane L. (Elsevier, 2025)
The polar metabolome of the medicinal plant Ammodaucus leucotrichus Coss. & Dur. has not been comprehensively characterised. In this study, the chemical composition of a water/methanol (4:1) extract of seeds was determined through a combination of UHPLC-MS and NMR techniques. Sixty compounds were identified from the extract with 36 of these confirmed using UHPLC-MS and/or NMR data while the remaining 24 were given putative identifications based on UHPLC-MS data. The compounds included lignans, terpenes, phenolics, flavonoids, and alkaloid derivatives together with some amino- and organic acids. Of these 2 terpenoids and 3 lignans were found to be novel and were isolated and structures determined by comprehensive NMR studies. A further novel lignan glycoside was tentatively identified. Together these data represent the most comprehensive profile of this traditional medicinal plant, providing an annotated profile that can form the basis of future correlative metabolomic investigations to determine active principles behind its reported bioactivities.
Keywords: Ammodaucus leucotrichus; Apiaceae; UHPLC-MS; NMR; Lignan; Terpene; Ammolactone-A; Ammodauside; Ammodaucic acid; Ammodolide; 3401 Analytical Chemistry; 34 Chemical Sciences; Dietary Supplements; Complementary and Integrative Health; Medicinal & Biomolecular Chemistry; 3404 Medicinal and biomolecular chemistry; 3405 Organic chemistry